Cage effects and rotational hindrance in the surface scattering of large (N 2) n clusters - Chaâbane, Nihed; Jundt, Gregor; Vach, Holger; Koch, Denise M; Peslherbe, Gilles H (International journal of mass spectrometry, 2002)
We present results from classical trajectory calculations of collisions of (N 2) n (64≤ n≤512) clusters with a graphite surface in order to deepen our understanding of energy transfer processes and cluster fragmentation dynamics. Translational and rotational distributions for the monomer products of evaporation are determined for incidence angles between 30 and 70°, at an incident velocity of 750±50 m s −1 and for two surface temperatures. Our molecular dynamics simulations, which employ a simple trapping/desorption model for describing the interactions between molecules and the surface, allow us to reproduce experimental results not only qualitatively, but also quantitatively. A detailed analysis of the scattering event shows that the monomer translational energy distributions can be well described by a single Boltzmann distribution, while the rotational distributions of scattered molecules are best represented by a sum of two distinct Boltzmann distributions. The two resulting rotational temperatures can be attributed to a significant cage effect occurring during the cluster–surface impact. As a result, monomers originating from the outskirts of the clusters evaporate rotationally hot, while monomers from the very interior of the cluster—which are subject to cage effects—tend to be rotationally colder. Absolute values of the rotational temperatures indicate that the hot monomers experience significant rotational hindrance when evaporating from their parent cluster.